‘Is there value for us in agriculture?’ A case study of youth participation in agricultural value chains in KwaZulu-Natal, South Africa - Geza, W.; Ngidi, M. S. C.; Mudhara, M.; Slotow, R.; Mabhaudhi, Tafadzwanashe (Informa UK Limited, 2023)
Developing countries in Africa face an unemployment crisis, with many unemployed youth. Agriculture has been identified as a strategic sector for employment creation targeted at youth, including those who may not have agriculture-related qualifications. However, various challenges limit the effectiveness of youth participation in the agriculture value chain. The study aimed to (i) determine youth awareness of agricultural value-chain opportunities, (ii) determine their perception of their role in the value chain, (iii) determine their perception of agricultural programs targeting youth and their opinions on who is responsible for attracting youth into agriculture and, (iv) to characterise the dynamics of youth empowerment in agriculture. Data was collected using focus group discussions and an online survey and analysed using SPSS and NVivo. Poor knowledge, low levels of awareness of agricultural value-chain activities and careers, and not meeting the minimum requirements for employment in processing and retail businesses were identified as key challenges. Most youth were interested in non-primary activities such as agro-processing, which are less labour-intensive and have a quicker return on investment than agricultural production. However, support services and programs for promoting youth participation in agriculture mainly focus on primary activities, signifying a mismatch between youth aspirations and current support. Understanding youth aspirations, perceptions and dynamics underpinning youth empowerment and participation in value chains is critical for promoting participation and formulating relevant and responsive policies. Additionally, improving access to information and building awareness of agricultural value chains is crucial in reducing barriers to entry. Policymakers should integrate agriculture and food systems knowledge into the primary education curriculum to promote youth awareness and evoke interest in agri-food system careers at an early age.